Changes in solvation during DNA binding and cleavage are critical to altered specificity of the EcoRI endonuclease - Robinson, Clifford R. (The National Academy of Sciences, 1998)
Restriction endonucleases such as EcoRI bind and cleave DNA with great specificity and represent a paradigm for protein–DNA interactions and molecular recognition. Using osmotic pressure to induce water release, we demonstrate the participation of bound waters in the sequence discrimination of substrate DNA by EcoRI. Changes in solvation can play a critical role in directing sequence-specific DNA binding by EcoRI and are also crucial in assisting site discrimination during catalysis. By measuring the volume change for complex formation, we show that at the cognate sequence (GAATTC) EcoRI binding releases about 70 fewer water molecules than binding at an alternate DNA sequence (TAATTC), which differs by a single base pair. EcoRI complexation with nonspecific DNA releases substantially less water than either of these specific complexes. In cognate substrates (GAATTC) k(cat) decreases as osmotic pressure is increased, indicating the binding of about 30 water molecules accompanies the cleavage reaction. For the alternate substrate (TAATTC), release of about 40 water molecules accompanies the reaction, indicated by a dramatic acceleration of the rate when osmotic pressure is raised. These large differences in solvation effects demonstrate that water molecules can be key players in the molecular recognition process during both association and catalytic phases of the EcoRI reaction, acting to change the specificity of the enzyme. For both the protein–DNA complex and the transition state, there may be substantial conformational differences between cognate and alternate sites, accompanied by significant alterations in hydration and solvent accessibility.